2016
DOI: 10.1017/s000748531600033x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of host nutritional quality on multiple components ofTrichogramma brassicaefitness

Abstract: 16For parasitoids, the host represents the sole source of nutrients for the developing immature. 17Subsequently, host quality is an important factor affecting immature development and the 18 resulting fitness of the emerging parasitoid, with impacts on fecundity, longevity and offspring 19 sex ratio. Host age is an integral component of host quality and a key factor in host selection by 20 the female parasitoid. The current study aimed to investigate the effect of decreasing host quality 21 (determined by incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 73 publications
4
23
0
Order By: Relevance
“…In our study, the egg to adult development of T. achaeae at 25 °C was completed in 8.83 d in E. kuehniella eggs, lower than the 10.4 d and 10.8 d recorded by Ghosh et al [ 51 ] and Manohar et al [ 52 ] in Corcyra cephalonica Stainton (Lepidoptera: Pyralidae) and T. absoluta eggs, respectively. These differences might be associated with the effect of the size and nutritional quality of the host egg on the preimaginal development and adult fitness of Trichogramma spp., as suggested by Kishani Farahani et al [ 74 ]. Our studies indicated that T. achaeae developed successfully from egg to adult in the temperature range of 15 °C to 30 °C.…”
Section: Discussionmentioning
confidence: 83%
“…In our study, the egg to adult development of T. achaeae at 25 °C was completed in 8.83 d in E. kuehniella eggs, lower than the 10.4 d and 10.8 d recorded by Ghosh et al [ 51 ] and Manohar et al [ 52 ] in Corcyra cephalonica Stainton (Lepidoptera: Pyralidae) and T. absoluta eggs, respectively. These differences might be associated with the effect of the size and nutritional quality of the host egg on the preimaginal development and adult fitness of Trichogramma spp., as suggested by Kishani Farahani et al [ 74 ]. Our studies indicated that T. achaeae developed successfully from egg to adult in the temperature range of 15 °C to 30 °C.…”
Section: Discussionmentioning
confidence: 83%
“…In this experiment and egg freezing experiment, lipid levels declined by 11%, glycogen levels declined by 18–33%, and sugar levels increased by 18–82%. In another egg-parasitoid system, a ~37% decline in protein and ~22% decline in triglyceride levels in host eggs was associated with decreased parasitoid fecundity and longevity ( Kishani Farahani et al 2016 ). Nevertheless, future experiments using frozen clusters should keep deployment times consistent across treatments in case it will affect natural enemy performance.…”
Section: Discussionmentioning
confidence: 99%
“…Egg quality may be especially important for egg parasitoids, since the developing parasitoid derives its nutrients only from the host. For example, host eggs with lower protein, glycogen, and triglyceride content produce Trichogramma (Hymenoptera: Trichogrammatidae) wasps with lower nutrient reserves, fecundity and longevity than higher quality host eggs ( Kishani Farahani et al 2016 ). A review by Abram et al (2017) revealed that most biological control research has focused on BMSB egg clusters rather than nymphs or adults.…”
mentioning
confidence: 99%
“…For this reason, the choice of host has profound implications for the emerging parasitoid and has been shown to impact an array of life history traits such as development time, emergence rate, longevity, size and sex ratio (e.g. Harvey et al, 2004;Colinet et al, 2005;Silva et al, 2008;Xu et al, 2008;Sidney et al, 2010;Kishani Farahani et al, 2016). However, the impact of the host on adult parasitoid thermal tolerance was unknown until this study.…”
Section: Discussionmentioning
confidence: 93%
“…Host quality is known to impact an array of life history traits including development time, adult size, fecundity, longevity and offspring sex ratio (e.g. Harvey et al, 2004;Ris et al, 2004;Colinet et al, 2005;Silva et al, 2008;Xu et al, 2008;Sidney et al, 2010;Kishani Farahani et al, 2016). However, how the host affects the physiological thermal tolerance of a generalist parasitoid is unknown.…”
Section: Introductionmentioning
confidence: 99%